Self-Regulated Learning of Pre-Service Teachers in Digital Learning Environments. - Zhang, Chengming; Hofmann, Florian; Kamran, Farrukh; Gläser-Zikuda, Michaela (Self-Regulated Learning – Insights and Innovations, 2024)
Nowadays, “being digital" has been largely realized, especially in education. The continuous renewal of Information Communication Technology (ICT) and Artificial Intelligence (AI) leads to an educational revolution. Therefore, teaching and learning activities are no longer restricted by time, space, CE and humans. As a result, future qualified teachers with high self-regulation competence and strong digital competence are in great need. However, research studies reveal that many teachers directly replicate traditional classrooms and fail to conduct virtual activities with possible digital resources and the application of AI. Confronted with such challenges, future teachers do often not accept AI and feel unprepared for future teaching. This chapter provides an overview of research theories, assessment techniques, and support instruments in related research area
Keywords: self-regulated learning; digital competence; AI acceptance; teacher education research